The Curtin Coaches: Benefits of an outreach tutoring program for first year pre-service teachers - Karnovsky, Saul; Flodin, Charles (FYHE, 2014)
The Curtin Coaches program represents a dynamic outreach opportunity for pre-service teachers enrolled in their first year of study at Curtin University to engage with school-aged students as classroom tutors. Research has shown that tutoring experiences can benefit both the students receiving support and those who tutor, particularly in settings where individuals are engaging in community support work. According to program feedback, participants were able to develop a range of profession-related skills such as relationship building and gain new knowledge such as understanding how students learn. These competencies are salient as they align with the newly implemented federal standards for graduate teachers. Understanding the benefits such outreach programs bring pre-service teachers is vital as the future of university funded school programs such as the Curtin Coaches is uncertain but the importance of Work Integrated Learning is increasing.